Servicios informativos para centros comerciales, usando tecnología bluetooth - Seris, Ricardo (2009)
The flexibility to develop applications that use transmission media such as wireless Bluetooth (BT), added to that most mobile devices (phones, PDAs, laptops, etc.) come with built-in support BT, makes us think about using BT technology to send ads. In this article we describe the different components and processes of a communication system via (BT) which provides advertising services. Such this services can be supplied in malls, airports, cinemas and can be adapted to any site that users focus with BT devices